2015
DOI: 10.1103/physrevb.91.094502
|View full text |Cite
|
Sign up to set email alerts
|

Chiral bosonic phases on the Haldane honeycomb lattice

Abstract: Recent experiments in ultracold atoms and photonic analogs have reported the implementation of artificial gauge fields in lattice systems, facilitating the realization of topological phases. Motivated by such advances, we investigate the Haldane honeycomb lattice tight-binding model, for bosons with local interactions at the average filling of one boson per site. We analyze the ground state phase diagram and uncover three distinct phases: a uniform superfluid (SF ), a chiral superfluid (CSF ) and a plaquette M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 135 publications
(240 reference statements)
5
67
0
Order By: Relevance
“…Looking toward the future, we anticipate that having the ability to induce a local structural transition to a superconducting phase with local probes will be a useful quantum nanotechnology workbench to design superconducting nanostructures for investigating both fundamental interest and practical applications of quantum electronics. We envision the ability to create networks of low dimensional superconducting structures, such as lines and dots, or create patterns to engineer designer bosonic systems with artificial gauge fields [55,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking toward the future, we anticipate that having the ability to induce a local structural transition to a superconducting phase with local probes will be a useful quantum nanotechnology workbench to design superconducting nanostructures for investigating both fundamental interest and practical applications of quantum electronics. We envision the ability to create networks of low dimensional superconducting structures, such as lines and dots, or create patterns to engineer designer bosonic systems with artificial gauge fields [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainty in the normalized flux is derived from the uncertainty in the island area, which was determined from the STM topographic profile in Fig. 3(e) [56]. …”
Section: Appendix D: Electrical Transport Measurementsmentioning
confidence: 99%
“…Using direct analogs of the fractional QHE (FQHE) in a topological flat band [17,18], evidence of bosonic FQHE has been demonstrated in a simple lattice model [19]. However, this simple replacement in a Chern insulator does not generate the expected bosonic QHE and the bosonic phase dominated by spinorbit coupling in the Haldane model becomes a chiral superfluid [20][21][22]. The realization of bosonic QHE in a simple lattice is achieved by combining correlated hopping and a background gauge field or the use of the lowest band of an optical flux lattice [23][24][25].…”
mentioning
confidence: 99%
“…1 As the system has the strong frustrations for the case of φ = 0, it is important to see if the phase diagram depends on the system size. In order to see this, we studied the system with (L x , L y ) = (6,6). No exact diaganalization results are available for this system size.…”
Section: A Low-temperature Phase Diagramsmentioning
confidence: 99%
“…A recent study reported its ground-state properties and low-energy excitations at unit filling 6 . In particular, we are interested in the hardcore boson limit where the on-site repulsive interaction U is very large (U → ∞).…”
Section: Introductionmentioning
confidence: 99%